ANALISIS KINERJA DANA BERGULIR TERHADAP PENGEMBANGAN USAHA MIKRO DAN KECIL - Mahfudz Mahfudz (Jurnal Dinamika Ekonomi & Bisnis, 2006)
AbstractThis research to evaluate the patterns of managing financials which run out through, 3 success achievement, they are succeedin sending, succeed in using and succed in returning, also to analyze the efforts to solve any problems of sending financial and make progress in processing "income generating" through the using offinancials runs out. The research held in six nominees regencies in profince Central Java which is carried out to 398 micro effort and small field nofarming. The data collection of primary carried out through survey of respondents based to questioner with items loaded materials consious of Effort of body shape, the sources offinancial efforts, distributing the financial run out, the use of financial  runs out, returning the debt also evaluated the success of financial run out. The result of research shows that as totally the financial distribution run out could so well, the run out financial run out financial could be used well, also the majority of financial run out user had returned it well and only the consequences of debt, this result claims that the management of run out financial in research regions showed the satisfield working. Keyword: Financial run out, 3 success of run out financial management